Association between Physical Health and Well-being: A Quasi-experimental Study - Villarino, Resti Tito; Villarino, Maureen Lorence; Temblor, Maria Concepcion; Bernard, Prosper; Plaisent, Michel (Journal of Liaquat University of Medical & Health Sciences, 2022)
OBJECTIVE: To determine the relationship between physical health and well-being among college students in a state university and private college. METHODOLOGY: The study used a quantitative method, utilizing a pretest-posttest study design on 178 college students. The test group received three months of the health and well-being program while the control continued their activities of daily living (ADL). Nutrition, physical activity, and sleep were measured using the adapted Canadian Community Health Survey - Annual Component–2021. Well-being was evaluated using the modified positive emotion, engagement, relationships, meaning, and accomplishments (PERMA) questionnaire. Phase 1 includes gathering the participants' socio-demographic profiles, and the research concludes with the evaluation of the program. SPSS v.27 was used to analyze the data. RESULTS: Multiple regression analysis results for engagement (r(176) = .26, p = .92), relationships (r(176) = .21, p = .06), accomplishments (r(176) = .22, p = .31), and the overall PERMA (r(176) = .13, p = .42) were greater than the significance level of 0.05. However, positive emotion (r(176) = .26, p = .006) and meaning (r(176) = .23, p = .02) results were less than the significance level of a=0.05 indicating evidence of significant relationship. CONCLUSION: The study has established that positive emotion and meaning are significantly related to physical activity, nutrition, and sleep. KEYWORDS: Physical health, wellness, online health, college students